2007
DOI: 10.1158/1055-9965.epi-06-0636
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA Methylation Level in Whole Blood as a Biomarker in Head and Neck Squamous Cell Carcinoma

Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) is commonly associated with tobacco and alcohol exposures, although dietary factors, particularly folate, and human papillomavirus, are also risk factors. Epigenetic alterations are increasingly implicated in the initiation and progression of cancer. Genome-wide (global) hypomethylation seems to occur in early neoplasia and is a feature of genomic DNA derived from solid tumor tissues, including HNSCC. This study aimed to determine whether global methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
259
10
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(310 citation statements)
references
References 50 publications
34
259
10
7
Order By: Relevance
“…17,21,33,37,38,39,46 For example, total 5-mC content in WBC was higher in males than females in one study, 33 but this result was not replicated in a larger study measuring 5-mC. 18 Of the repetitive elements, LINE-1 has been investigated more frequently and was associated with lower levels in females compared to males in most 17,21,[37][38][39]46 but not all studies. 41 In contrast, there has been no consistent pattern associated with Alu methylation.…”
Section: Wbc Methylation and Diseasementioning
confidence: 97%
See 1 more Smart Citation
“…17,21,33,37,38,39,46 For example, total 5-mC content in WBC was higher in males than females in one study, 33 but this result was not replicated in a larger study measuring 5-mC. 18 Of the repetitive elements, LINE-1 has been investigated more frequently and was associated with lower levels in females compared to males in most 17,21,[37][38][39]46 but not all studies. 41 In contrast, there has been no consistent pattern associated with Alu methylation.…”
Section: Wbc Methylation and Diseasementioning
confidence: 97%
“…Less is known about changes in WBC DNA methylation levels and cancer risk, although studies are rapidly emerging. Specifically, at least eight studies measuring overall WBC global DNA methylation in different cancer types including colon, 14,15 bladder, [16][17][18] stomach, 19 breast, 20 and head and neck cancer 21 have found an elevated risk for cancer between those in the lowest quantile of global DNA methylation compared to those in the highest quantile of risk; the association was statistically significant in six of the studies (see Fig. 1 for summary).…”
Section: Wbc Methylation and Diseasementioning
confidence: 99%
“…4,5 DNA methylation measured in LINE-1 sequences has been considered a surrogate marker for global genome methylation. 6 Although most epigenetic studies have been focused on cancer, 7,8 , previous studies have suggested that DNA methylation in these LINE-1 elements may play a role in other complex human diseases, such as cardiovascular disease or diabetes. [9][10][11][12] However, there are still many unresolved issues about the role of epigenetic changes in the study of complex diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on epigenetics of mammalian preimplantation embryos found that transposable elements show a similar dynamic trend towards global methylation (Guo et al 2014). Among all types of retrotransposons, L1 is mostly studied and has been used for indicating methylation changes in cancer cells (Hsiung et al 2007), and a recent study of global methylation found a good correlation between L1 methylation and total amount of 5-methylcytosine measured by liquid chromatography mass spectrometry in murine cells and tissues (Newman et al 2012).…”
mentioning
confidence: 99%